2011
DOI: 10.1176/appi.ps.62.4.418
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Probation in Forensic Assertive Community Treatment

Abstract: Objective Forensic assertive community treatment (FACT) is an adaptation of the assertive community treatment model designed to prevent criminal recidivism through criminal justice collaborations. A national survey was conducted to examine FACT collaborations with probation departments. Methods Members of the National Association of County Behavioral Health and Developmental Disability Directors were surveyed to identify FACT programs. Programs reporting collaborations with probation departments were contact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Lamberti, Deem, Weisman, and LaDuke (2011) conducted a survey of FACT teams nationwide which showed that most programs feature at least some degree of collaboration between mental health professionals and criminal justice authorities, which can be formal (as would be the case when a parole or probation officer is a member of the clinical team) or informal (as would be the case when mental health and criminal justice officials share information and collaborate on treatment decisions). In either variation, the collaboration makes possible the use of legal leverage to enforce treatment engagement.…”
Section: Resultsmentioning
confidence: 99%
“…Lamberti, Deem, Weisman, and LaDuke (2011) conducted a survey of FACT teams nationwide which showed that most programs feature at least some degree of collaboration between mental health professionals and criminal justice authorities, which can be formal (as would be the case when a parole or probation officer is a member of the clinical team) or informal (as would be the case when mental health and criminal justice officials share information and collaborate on treatment decisions). In either variation, the collaboration makes possible the use of legal leverage to enforce treatment engagement.…”
Section: Resultsmentioning
confidence: 99%
“…There is an increasing number of partnerships between specialty mental health organizations and community corrections. For instance, forensic assertive community treatment (FACT), an offshoot of the assertive community treatment (ACT) movement, seeks to improve outcomes for justice-involved clients with severe mental illness through collaboration between mental health treatment providers and criminal justice agencies, such as probation and parole (Lamberti, Deem, Weisman, & LaDuke, 2011). Such partnerships promote treatment adherence via legal influence and provide criminal justice agencies with access to rehabilitative alternatives to standard sanctions (Lamberti et al, 2011(Lamberti et al, , 2014.…”
Section: Specialty Mental Healthmentioning
confidence: 99%
“…For instance, forensic assertive community treatment (FACT), an offshoot of the assertive community treatment (ACT) movement, seeks to improve outcomes for justice-involved clients with severe mental illness through collaboration between mental health treatment providers and criminal justice agencies, such as probation and parole (Lamberti, Deem, Weisman, & LaDuke, 2011). Such partnerships promote treatment adherence via legal influence and provide criminal justice agencies with access to rehabilitative alternatives to standard sanctions (Lamberti et al, 2011(Lamberti et al, , 2014. Although there are differences between individual programs (e.g., whether they admit individuals with who have committed certain types of offenses), there is also significant common ground (Lamberti et al, 2011).…”
Section: Specialty Mental Healthmentioning
confidence: 99%
See 2 more Smart Citations